Pulmonary Vascular Research Institute GoDeep: A meta‐registry merging deep phenotyping datafrom international PH reference centers. (24th August 2022) - Majeed, Raphael W.; Wilkins, Martin R.; Howard, Luke; Hassoun, Paul M.; Anthi, Anastasia; Cajigas, Hector R.; Cannon, John; Chan, Stephen Y.; Damonte, Victoria; Elwing, Jean; Förster, Kai; Frantz, Robert; et al.
Abstract: The Pulmonary Vascular Research Institute GoDeep meta‐registry is a collaboration of pulmonary hypertension (PH) reference centers across the globe. Merging worldwide PH data in a central meta‐registry to allow advanced analysis of the heterogeneity of PH and its groups/subgroups on a worldwide geographical, ethnical, and etiological landscape (ClinTrial. gov NCT05329714). Retrospective and prospective PH patient data (diagnosis based on catheterization; individuals with exclusion of PH are included as a comparator group) are mapped to a common clinical parameter set of more than 350 items, anonymized and electronically exported to a central server. Use and access is decided by the GoDeep steering board, where each center has one vote. As of April 2022, GoDeep comprised 15, 742 individuals with 1.9 million data points from eight PH centers. Geographic distribution comprises 3990 enrollees (25%) from America and 11, 752 (75%) from Europe. Eighty‐nine perecent were diagnosed with PH and 11% were classified as not PH and provided a comparator group. The retrospective observation period is an average of 3.5 years (standard error of the mean 0.04), with 1159 PH patients followed for over 10 years. Pulmonary arterial hypertension represents the largest PH group (42.6%), followed by Group 2 (21.7%), Group 3 (17.3%), Group 4 (15.2%), and Group 5 (3.3%). The age distribution spans several decades, with patients 60 years or older comprising 60%. The majority of patients met an intermediate risk profile upon diagnosis. Data entry from a further six centers is ongoing, and negotiations with >10 centers worldwide have commenced. Using electronic interface‐based automated retrospective and prospective data transfer, GoDeep aims to provide in‐depth epidemiological and etiological understanding of PH and its various groups/subgroups on a global scale, offering insights for improved management.